(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Arteriovenous Malformations (AVMs) are rare vascular anomalies characterized by abnormal arteriovenous shunts, typically lacking a connecting capillary bed. These lesions often result from embryogenic vascular developmental abnormalities. AVMs can manifest with various clinical symptoms, including hemorrhage, seizures, and neurological deficits. Here, we present a case of a 10-year-old male with an AVM involving the right mandible, presenting with intraoral bleeding, facial asymmetry, and engorged veins. The patient underwent excision of the lesion with right hemimandibulectomy, and no postoperative complications were observed. AVMs of the face are infrequent, but when they occur in the mandibular region, hemorrhage is a common clinical presentation. Treatment modalities include microsurgery, embolotherapy, and radiosurgery. However, recurrence remains a concern, particularly in pediatric cases. This case underscores the importance of recognizing AVMs in pediatric patients to facilitate early diagnosis and appropriate management, which can alleviate symptoms, prevent life-threatening complications and reduce mortality. Despite their rarity, AVMs should be considered in the differential diagnosis of facial asymmetry and intraoral bleeding, especially in children. Timely intervention, as demonstrated in our case, can improve outcomes and enhance the quality of life for affected individuals. JCMCTA 2023 ; 34 (2) : 153-156